2013
DOI: 10.1038/emboj.2013.230
|View full text |Cite
|
Sign up to set email alerts
|

Pds5B is required for cohesion establishment and Aurora B accumulation at centromeres

Abstract: Cohesin mediates sister chromatid cohesion and contributes to the organization of interphase chromatin through DNA looping. In vertebrate somatic cells, cohesin consists of Smc1, Smc3, Rad21, and either SA1 or SA2. Three additional factors Pds5, Wapl, and Sororin bind to cohesin and modulate its dynamic association with chromatin. There are two Pds5 proteins in vertebrates, Pds5A and Pds5B, but their functional specificity remains unclear. Here, we demonstrate that Pds5 proteins are essential for cohesion esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
119
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 69 publications
12
119
0
Order By: Relevance
“…Another possibility is that STAG2 stabilizes the positioning of cohesin rings on centromeric chromatin to create platforms for the appropriate phosphorylation of histone subunits and the recruitment of centromeric-binding proteins. These views are consistent with a recent report showing that the cohesininteracting protein Pds5b also promotes Aurora B localization at centromeres (Carretero et al, 2013), although it affected haspin kinase activity, and not Bub1. This indicates that cohesin structure and function at centromeres is subject to regulation by multiple factors to ensure faithful chromosome segregation.…”
Section: Resultssupporting
confidence: 82%
“…Another possibility is that STAG2 stabilizes the positioning of cohesin rings on centromeric chromatin to create platforms for the appropriate phosphorylation of histone subunits and the recruitment of centromeric-binding proteins. These views are consistent with a recent report showing that the cohesininteracting protein Pds5b also promotes Aurora B localization at centromeres (Carretero et al, 2013), although it affected haspin kinase activity, and not Bub1. This indicates that cohesin structure and function at centromeres is subject to regulation by multiple factors to ensure faithful chromosome segregation.…”
Section: Resultssupporting
confidence: 82%
“…In either case, our results imply that the critical DNA-tethering reaction(s) require Esco1's ongoing association with cohesin, in addition to its acetylation of Smc3. Because Smc3 acetylation depends on cohesin's ATPase activity, chromatin loading (51), and Pds5 (19,52,53), our results suggest that Esco1 not only modifies cohesin soon after its topological linkage to DNA, but in fact remains bound to the cohesin-DNA complex, possibly through chromatin-specific interactions with Pds5 and Smc3's ATPase domain. Although Pds5′s precise effects on cohesin are still enigmatic, one of its key roles is to provide a regulatory interface for fine-tuning cohesin's association Cohesin recruits Esco1 during or shortly after its ATPase-dependent loading, via the latter's A-box and B-box motifs.…”
Section: Discussionmentioning
confidence: 89%
“…Acetylation neutralizes the anticohesive activity of Wapl and Pds5 (16)(17)(18)(19), which may activate a DNA exit gate at the Smc3-Rad21 interface (20)(21)(22)(23). Neutralization of Wapl-Pds5 not only builds cohesion during S phase but also promotes fork progression and restart (24,25), and in higher organisms is supported by an additional Wapl antagonist called sororin (26,27).…”
mentioning
confidence: 99%
“…Carretero et al demonstrated that Pds5B-deficient MEF cells showed a decreased activation of Aurora B and Haspin at centromeres and an impaired centromeric localization of Aurora B suggesting that Pds5B may be involved in the recruitment of Haspin on centromeres [33]. The recruitment of Haspin by Pds5B has been confirmed in human cell lines by Hindriksen et al [26].…”
Section: How Is Haspin Recruited Onto Chromosomes?mentioning
confidence: 95%